Guiding the Behaviour of Children and Young People - Lindon, Jennie (London : Hodder Education, 2009)
Written by one of the country's leading child care authors, 'Guiding the Behaviour of Children and Young People' is a resource for child care students and experienced practitioners looking for a more detailed and thorough exploration on the subject of behaviour.
Includes bibliographical references and index.
Keywords: Child development; Child care; Child psychology; Child Care